Upaya Hukum Peninjauan Kembali Dalam Perkara Perdata (Studi Putusan Mahkamah Agung Nomor 118/PK/Pdt/2018) - Farangga Harki Ardiansyah; Alfitra Alfitra; Tresia Elda (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
This study aims to determine the legal position of legal reconsideration efforts as extraordinary legal remedies. Legal reconsideration efforts are the last legal remedies that can be filed in the judicial system in Indonesia and of course their extraordinary nature requires special supervision in matters of regulation. This research is a normative legal research using a statute approach or a statutory approach to understand the concept of legal reconsideration efforts in civil cases as regulated in statutory regulations as an effort to bring closer to the problems studied based on the rules, norms and rules according to the object under study. The results of the research show that legal review is an extraordinary remedy which in the process requires clear restrictions, especially in civil cases, which still requires firm and clear regulations regarding the procedure and how many times it can be filed.Keywords: Reconsideration, Civil, Legal Efforts, PK, Second Reconsideration